P231 Audit of pre-hospital oxygen therapy by North West Ambulance Service (NWAS) 1 year after publication of new JRCALC guidance for oxygen use. (16th November 2010) - Matthews, A; Gavin, C; O'Driscoll, B R
Abstract : We audited oxygen use amongst 443 cases brought to the "majors" A&E area of a university hospital by NWAS ambulance teams in May–July 2010. We compared the findings with our 2007 audit conducted before publication of the BTS emergency oxygen guideline in 2008 and JRCALC guidance in 2009 (Hale K. Emerg Med J 2008;25 :773). Results: 90% of cases had oximetry recorded by ambulance teams in 2007, rising to 96% in 2010. 19% of cases were hypoxic in 2010 and 27% were given oxygen compared with 34% in 2007 (see Abstract P231 Table 1 ). The proportion given oxygen fell from 31% in the initial 4 weeks to 24% in the final 5 weeks of the audit when feedback was given to ambulance teams. The "ideal" figure for these cases was about 21% based on JRCALC guidance. 86% of cases were treated in accordance with JRCALC guidance in terms of receiving or not receiving oxygen and 73% were treated in full compliance (correct device and flow rate). The overall compliance rate was 4.4% higher (95% CI –2.3% to 11.0%) during the feedback period and full compliance rose by 9.9% (95% CI 1.6 to 18.2%) following feedback. Eight percent of cases received oxygen inappropriately and 3% were denied oxygen inappropriately. Our audit revealed that NWAS ambulance crews were unable to give controlled oxygen to COPD cases because Venturi masks were not carried. Several COPD cases received high dose oxygen from nebuliser masks throughout the journey because air driven nebulisers and nasal cannulae were not available. Only four of 14 cases with AECOPD had SpO2 <88% but 12 were given oxygen and 10 developed SpO2 >92%. Conclusions: The proportion of NWAS cases receiving oxygen in pre-hospital care has fallen from 34% in 2007 to 27% in 2010 following publication of BTS and JRCALC oxygen guidelines. 86% of cases were treated in broad compliance with JRCALC guidance and 73% were in full compliance. There is potential for further slight reduction in oxygen use in ambulances, especially for COPD patients. This may be enhanced by feedback to ambulance crews and by providing a wider range of oxygen delivery equipment in ambulances.